ChemInform Abstract: Palladium‐Catalyzed Allylic Alkylation of Allyl Dienol Carbonates: Reactivity, Regioselectivity, Enantioselectivity, and Synthetic Applications. Issue 4 (28th January 2014) - Arseniyadis, Stellios; Fournier, Jeremy; Thangavelu, Saravanan; Lozano, Oscar; Prevost, Sebastien; Archambeau, Alexis; Menozzi, Candice; Cossy, Janine
Abstract Review: 144 refs.